2006
DOI: 10.1186/1748-7161-1-10
|View full text |Cite
|
Sign up to set email alerts
|

Painful rib hump: a new clinical sign for detecting intraspinal rib displacement in scoliosis due to neurofibromatosis

Abstract: Spine surgeons should be aware of intraspinal rib displacement in scoliotic curves in neurofibromatosis. Painful rib hump is a valuable diagnostic tool for this rare clinical entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Despite being neurologically intact in most reported cases, impending paraplegia is generally emphasized and may be elicited by traumatic events, use of a brace compressing the apical ribs, or surgical maneuvers [4,6,14]. Nowadays, this concern is increased with the advent of modern instrumentation techniques that provide greater correction [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite being neurologically intact in most reported cases, impending paraplegia is generally emphasized and may be elicited by traumatic events, use of a brace compressing the apical ribs, or surgical maneuvers [4,6,14]. Nowadays, this concern is increased with the advent of modern instrumentation techniques that provide greater correction [8].…”
Section: Discussionmentioning
confidence: 99%
“…Bony dysplasia involving foraminal enlargement, penciling, and rotation of the apical ribs, along with significant multiplanar kyphoscoliotic deformity is regarded to contribute mechanically to allow the bony invasion [2]. This rare clinical entity can be suspected by palpation of a painful rib hump proposed by Gkiokas [6] and further be proven by CT and MRI scans.…”
Section: Introductionmentioning
confidence: 99%
“…Spindling of the transverse processes, foraminal enlargement, saccular dilatations, and pencilling of vertebral margins and apical ribs may contribute to costovertebral subluxation and dislocation of the rib head towards the neural foramen. 11,13,14 Spinal deformities of NF generally progress rapidly and cause serious cosmetic problems. In some cases, during the first diagnosis or during follow-up, some neurologic deficits can be seen.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven studies with 18 involved patients have been previously reported [3][4][5][6][7][8][9][10][11][12][13] (Table 1). These patients were remarkably similar: there were 10 males and 8 females with a mean age at presentation of 14.1 years (range: 5 to 41 y).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Although enlargement of the intervertebral foramina on the convexity of the curve can result in subluxation or penetration of a rib head into the spinal canal, it is rare with only 18 cases reported in the orthopaedic literature (Table 1). [3][4][5][6][7][8][9][10][11][12][13] We present a case of an adolescent male with NF-1 and severe dystrophic kyphoscoliosis with subluxation of 2 adjacent rib heads into the spinal canal, one of which was not apparent on the initial preoperative imaging.…”
mentioning
confidence: 99%